1987
DOI: 10.1002/jcp.1041310304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute serum depletion on Na+ ‐K+ homeostasis in cultured human skin fibroblasts

Abstract: In order to elucidate changes in cell transport behavior of cultured human skin fibroblasts in response to acute serum depletion, we performed uptake and washout of 22Na+ and 86Rb+ as well as measurements of the intracellular Na+ and K+ levels in the presence and absence of ouabain. Pronounced and lasting increase in cellular Na+ and decrease in K+ were observed after removal of fetal bovine serum (FBS) from the medium. The sum of the Na+ and K+ contents (nEq/10(5) cells) was lower in FBS-free medium (mean +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
1

Year Published

1988
1988
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 28 publications
(43 reference statements)
4
24
1
Order By: Relevance
“…Whereas the k% values are derived from a model that is dependent on values of intracellular Na + concentration, the ki is independent of this parameter. In previous investigations we found that the first and fastest exponent of "Na + washout from cultured rat fibroblasts and vascular smooth muscle cells 3 ' " as well as human skin fibroblasts 16 primarily represented the Na + -K + pump and its respective cellular compartment, inasmuch as subjecting these cells to ouabain or K + -deficient medium resulted in essentially complete disappearance of the fastest component. Moreover, based on the equilibrium distribution ratio of ^Na + between the medium and the cellular milieu at the initiation of the washout experiments, the calculated cellular Na + concentrations agreed quite well with direct measurements of the ion using atomic absorption spectrometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the k% values are derived from a model that is dependent on values of intracellular Na + concentration, the ki is independent of this parameter. In previous investigations we found that the first and fastest exponent of "Na + washout from cultured rat fibroblasts and vascular smooth muscle cells 3 ' " as well as human skin fibroblasts 16 primarily represented the Na + -K + pump and its respective cellular compartment, inasmuch as subjecting these cells to ouabain or K + -deficient medium resulted in essentially complete disappearance of the fastest component. Moreover, based on the equilibrium distribution ratio of ^Na + between the medium and the cellular milieu at the initiation of the washout experiments, the calculated cellular Na + concentrations agreed quite well with direct measurements of the ion using atomic absorption spectrometry.…”
Section: Discussionmentioning
confidence: 99%
“…16 Thus, the ouabain-sensitive Na + and K + (Rb + ) transport may not be sensitive and reliable indictors for the Na + -K + pump activity. One possible explanation for the observed differences in fibroblasts between blacks and whites could relate to differing effects of the cardiac glycoside on Na + -K + pump independent transports.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular Na ' and K t contents were not changed by the phorbol ester. We conclude that FBS removal raises the cellular Na+ content, and enhances "Rb+ efflux, through a calmodulin-dependent pathway activated by calcium influx.Removal of fetal bovine serum (FBS) causes marked changes in the Nat and K+ homeostasis of cultured human fibroblasts (Dall'Asta et al, 1986;Hopp et al, 1987). In a previous study (Hopp et al, 19871, with cultured human skin fibroblasts, we showed that FBS removal resulted in a 3 4 times increase in the intracellular Na+ concentration caused by an accelerated uptake rate and decreased efflux rate constant for the ion.…”
mentioning
confidence: 91%
“…Serum is also an important factor in maintaining cell function in many cell lines, and its deprivation can induce striking alterations in cell function. For example, removal of FBS from culture medium can cause a significant increase in the intracellular Na ϩ and a decrease in intracellular K ϩ in fibroblasts [Hopp et al, 1987]. Moreover, the mitogenic effect of serum may be responsible for some pathological alterations as well.…”
mentioning
confidence: 99%